Design of Interactive Media for World of Mathematics using MDLC Method - Bernadhed; Haryoko; Dhimas Adi Satria; Nadea Cipta Laksmita; Rifki Arifianto (International Journal of Informatics and Computation, 2025)
Adopting recent technological approaches can leverage learning activities in schools, specifically by using interactive learning media. However, the use of interactive media is still rarely implemented in primary schools that deliver educational material using cooperative learning methods, lectures, and simple videos. It may cause students to quickly become bored and struggle to understand the material on whole numbers and measurement. In this study, we adopted the MDLC method for creating the interactive media application. Data collection was conducted through direct interviews with teachers. The results of the feasibility aspect testing indicate that the developed interactive learning media received a score of 89.00%, categorizing it as very feasible, and the results of the material comprehension aspect testing show a Likert scale result of 81.5789474%, categorizing it as very well understood.